Open data for tourism: the case of Tourpedia. (24th June 2019) - Lo Duca, Angelica; Marchetti, Andrea
Abstract : Purpose: This paper aims to describe Tourpedia, a website about tourism, built on open data provided by official government agencies. Tourpedia provides data under a public license. Design/methodology/approach: Tourpedia is built upon a modular architecture, which allows a developer to add a new source of data easily. This is achieved through a simple mapping language, namely, Tourpedia mapping language, which maps the original open data set model to the Tourpedia data model. Findings: Tourpedia contains more than 70.000 accommodations, downloaded from open data provided by Italian, French and Spanish regions. Research limitations/implications: Tourpedia presents some limitations. First, extracted data are not homogeneous and often they are incomplete or wrong. Second, Tourpedia contains only accommodations. Finally, at the moment Tourpedia covers only some Italian, French and Spanish regions. Practical implications: The most important implication of Tourpedia concerns the construction of a single access point for all Italian, French and Spanish open data about accommodations. In addition, a simple mechanism for the integration of new sources of open data is defined. Social implications: The current version of Tourpedia opens also the road to three new possible social scenarios. First, Tourpedia could be transformed into an open source of updated information about tourism. Second, Tourpedia could be empowered to support tours, which include some tourist attractions and/or events and suggest the nearest accommodations. Finally, Tourpedia may help tourists to discover unknown places. Originality/value: Tourpedia constitutes an access point for data sets providers, application developers and tourists because it provides a unique website. Abstract : 开放旅游数据：Tourpedia案例 摘要 研究目的: 本论文介绍了Tourpedia, 一种以政府提供的开放数据为基础建立的旅游网站。Tourpedia通过公共执照来提供数据。 研究设计/方法/途径: Tourpedia采用模块型结构建设而成, 方便开放商增加新数据源。这种设计通过简单映射语言, 即Tourpedia Mapping Language（TML）, 使得原开放数据模型映射到Tourpedia Data Model（TDM）。 研究结果: Tourpedia包含70, 000多家住宿服务, 可从意大利、法国、和西班牙国家区域提供的开放数据中下载。 研究理论限制/意义: Tourpedia有一些限制。首先, 其数据并非均质而且很多情况下不完整或者错误。第二, Tourpedia只包含住宿业数据。最后, 目前Tourpedia只包含一些意大利、法国、和西班牙国家区域的数据。 研究实践意义: Tourpedia最重要的实践启示就是其通过单一信息渠道以涵盖所有意大利、法国、和西班牙国家区域关于住宿业的开放数据。此外, 新源开放数据的整合机制简单。 研究社会意义: 当前Tourpedia版本展开了三种社会场景的可能。首先, Tourpedia可以被改造成更新版的旅游信息开放数据源。第二, Tourpedia可以被用来支撑旅游活动, 包括提供一些游客景点和/或活动和就近住宿信息等。最后, Tourpedia可以帮助游客探索未知旅游目的地。 研究原创性: Tourpedia是一个独特的网站, 作为数据源, 为数据提供者、应用程序开发者、和游客提供便利。